China’s Efforts to Peak Carbon Emissions: Targets and Practice - Ying CAO; Xiaomei Li; Haoben YAN; Shuya KUANG (Chinese Journal of Urban and Environmental Studies, 2021)
According to the statement of President Xi Jinping at the general debate of the 75th session of the United Nations General Assembly, China aims to have CO2 emissions peak before 2030. Regions are the major units undertaking carbon emissions control. The achievement of the national emission peaking target requires the participation of all regions. However, regions still need to rationally judge their peaking targets and paths and enhance their basic capabilities while promoting carbon emissions peak. Besides, China should step up its macro-guidance for regions to peak carbon emissions in terms of top-level design, mechanisms improvement, and overall coordination.